Interest and Factors Affecting Student in Choosing Social Departments - Yarnefi, Yarnefi; Kartikowati, Sri; Gimin, Gimin (FKIP-Universitas Riau, 2019)
The low interest of students choosing social studies majors (IPS) at the National High School is thought to be a problem that originates from within students and outside the student's self. The purpose of this study was to determine the factors that influence students' interest in choosing a social studies major at SMA 2 Tambang, in Kampar Regency, Riau Province. The population in this study were all students of class XI IPS, amounting to 170 people. The sample was determined using propotional random sampling to obtain 119 people. The data analysis technique used is Path Analysis. The results of the analysis show that the family environment and school environment have a positive and significant effect on the ideals of choosing an IPS major. School ideals and environment have a positive and significant effect on the interest in choosing an IPS major. While the family environment has a significant effect on the interest in choosing an IPS major. However, there is a negative influence of the family environment on the interest of students choosing social studies majors, due to the low level of family education. Therefore parents are expected to be able to provide support so that their children are more interested in choosing social studies majors. The school is expected to further improve socialization to add information and provide an overview to students about social studies majors.